“Everyone Has Their Own Places”: Mapping as a Storied Approach to the Study of Youth Identity - Spring, Erin (Language and Literacy / Langue et littératie, 2021)
This article highlights part of my work with ten 16 and 17-year-olds at two Canadian secondary schools. My multiple case study sought to make visible my participants’ stories of place: how did they construe the role of place within their own lives? How did they record their journeys within, through, and between places? I share how my participants articulated their place-identities as dynamic encounters rather than fixed surfaces (Massey, 2005; Ingold, 2016). Employing story-mapping as a research method encouraged my participants to articulate their lives in their own terms, affording me the opportunity to understand how they negotiated their identities.